Pemetaan Potensi Geografis Pengembangan Peternakan Ayam Ras Petelur di Kecamatan Lintau Buo Kabupaten Tanah Datar - Fitri, Annisa Ladia; Novio, Rery (Al-DYAS, 2025)
This study aims to map the geographical potential for the development of layer chicken farming in Lintau Buo District, Tanah Datar Regency. The method used is the weighted overlay method, which works by overlaying multiple maps representing various parameters of an area's conditions. Each parameter is assigned a weight based on its importance using the Analytic Hierarchy Process (AHP) method. The alternative data used in this study consists of four nagari in Lintau Buo District: Nagari Pangian, Nagari Tigo Jangko, Nagari Buo, and Nagari Taluak. The research results indicate that Lintau Buo District has varying potential for poultry farming development. Nagari Pangian has a high-potential area of 391 hectares and a medium-potential area of 2,317 hectares. Nagari Tigo Jangko dominates the high-potential classification with an area of 3,514 hectares, while the medium-potential area covers 857 hectares, making it an ideal region for large-scale poultry farming. Meanwhile, Nagari Buo falls entirely within the medium-potential category, covering 906 hectares. Nagari Taluak has a high-potential area of 417 hectares and a medium-potential area of 3,125 hectares. These findings suggest that the development of layer chicken farming in Lintau Buo District should integrate geographical factors and regional carrying capacity to ensure sustainability and productivity.